Are Brain Natriuretic Peptide Levels Related to Flow through Autologous Aterio-Venous Fistulae for Chronic Haemodialysis? - Suttie, Stuart A; Mofidi, Reza; Bagul, Anil; Babber, Adarsh; Coats, Maria; Ross, Rose; Steedman, Scott; Levison, Rosie; Severn, Alison; Howd, Alison; Struthers, Alan; Nagy, Janos; et al. (Department of Surgery, UKM Medical Centre, 2012)
Formation of arterio-venous-fistulae (AVF) may exacerbate cardiac failure in the ever increasing, elderly population on haemodialysis. Brain Natriuretic Peptide (BNP) may prove a useful marker of cardiac failure in this population. We aimed to determine effect of creation of an AVF and flow in AVF on BNP levels. Ten patients undergoing primary formation of an upper limb autologous AVF (pre-dialysis), were recruited. Serum BNP (pg/ml) and flow in AVF (cm3/s) were documented pre-operatively, and then 2, 6 and 12 weeks post-operatively. The relationship between flow and BNP levels was assessed. Ten patients (6 male), mean age of 66yrs were recruited. Five patients had a radio-cephalic and 5 had a brachio-cephalic AVF formed. There was no correlation between BNP levels and flow within the AVF (r=0.34, p=0.28) at any time point. There was a general trend towards increased flow in the AVF over time, with only the change between flow at 2-weeks and 3-months postoperatively reaching significance, p=0.043. There was a general trend for BNP to fall over time in the postoperative period, with no significant change between the postoperative sampling time points. BNP levels do not correlate with flow across an AVF.